UNLEASH YOUR POTENTIAL - Rehita Hasian Batubara; Tiawan Tiawan; Muhammad Nugraha; Musawarman Musawarman; Heti Mulyani; Halimil Fathi; Muhammad Lulu Latif Usman Usman; Widya Andayani Rahayu; Salsabila Fitrania Utami (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
English and Mathematics are fields of science that attract a lot of student interest, every child in Indonesia gets an English and Mathematics education. Mathematics is the basis of various exact fields such as computer science, robotics, and other exact sciences. English is a universal language that is currently used in various countries in the world. Indorama Engineering Polytechnic held a webinar with the theme Unleash Your Potential, it is hoped that after this webinar event participants can improve their abilities and also unlock their potential in the fields of Mathematics and English.